Pemberian Diet Tinggi Protein pada Pasien Diabetes Mellitus Tipe 2 dengan Ulkus Gangren Pedis dan Hipokalemia: Sebuah Laporan Kasus - Yasmin Halim Bahasuan; Farapti Farapti (Universitas Airlangga, 2024)
Background: Diabetes mellitus is a serious condition caused by increased blood glucose levels due to insufficiency of the insulin hormone in maintaining blood sugar balance in the body. In certain cases, type 2 diabetes mellitus can result in gangrene, which is a soft tissue infection characterized by muscle tissue death or myonecrosis caused by gram-positive bacteria. The Standardized Nutrition Care Process (PAGT) is carried out by providing a DM diet with high-protein diet principles to accelerate the healing of gangrene wounds in patients. Objectives: This article aims to determine the process of standardized nutritional care for type 2 diabetes mellitus patients with gangrene ulcers and hypokalemia who use a high protein diet. Methods: The case study was conducted in November 2023 on inpatients at X Hospital, Gresik City. Results: After monitoring and evaluation, the results showed that food intake had increased from 40% on the first day to 50.2% of total intake on the third day of intervention. However, it had not reached the target (<80%) due to post-operative weakness. Complaints of abdominal pain were felt on the last day, blood pressure decreased from normal at 120/80 to low on the second and third days due to unstable physiological conditions after surgery. Conclusions: The patient's condition has not fully recovered. The results of biochemical and physical/clinical monitoring still show unstable changes. However, there has been an increase in food intake even though targets for several macronutrients have not been achieved.